Blonanserin vs risperidone in Japanese patients with schizophrenia: A post hoc analysis of a phase 3, 8‐week, multicenter, double‐blind, randomized controlled study - Philip D. Harvey; Hiroshi Nakamura; Sadanori Miura (Wiley, 2020)
Abstract Objective To report the efficacy and safety of blonanserin in patients with schizophrenia compared with risperidone in a Japanese multicenter, randomized, double‐blind study based on post hoc sensitivity analysis in addition to the previous results reported by Miura and discuss the current approaches for schizophrenia treatment. Methods Of 302 patients randomized, 156 received blonanserin (8‐24 mg/d) and 145 received risperidone (2‐6 mg/d) for 8 weeks. Efficacy variables included the Positive and Negative Syndrome Scale (PANSS) total score for the primary outcome, PANSS subscale, Brief Psychiatric Rating Scale (BPRS), and Clinical Global Impression‐Improvement (CGI‐I) for secondary outcomes. Safety variables included treatment‐emergent adverse events, Drug Induced Extrapyramidal Symptoms Scale scores, laboratory data, vital signs, electrocardiogram, etc Results Blonanserin was not inferior to risperidone in the change in PANSS total score at a non‐inferior margin of −7 (intergroup difference, −0.46; 95% CI, −4.40 to 3.48). Post hoc analyses wholly supported the primary result. No major difference was found in the changes in BPRS scores and the improvement rate on CGI‐I between the drugs. The incidence of adverse events was similar in the two drugs. Blonanserin was associated with a lower risk of prolactin increase, weight gain, and orthostatic hypotension compared with risperidone. However, blonanserin was associated with a higher incidence of akathisia and excitability compared with risperidone. Most of the adverse events were mild to moderate in severity with no specific events of predominant high severity in the both drugs. Conclusions Blonanserin exerted the similar efficacy to risperidone in both positive and negative symptoms in schizophrenia with a lower risk of prolactin increase, weight gain, and orthostatic hypotension compared with risperidone. Blonanserin will serve as a favorable treatment option for schizophrenia in daily clinical practice.